Electrical Conductivity of Carbon Electrodes by Mixing Carbon Rod and Electrolyte Paste of Spent Battery - Suka Handaja; Heru Susanto; Hermawan Hermawan (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
As a consequence of increasing battery use, spent batteries are increasingly contributing to solid waste. This situation has the potential to create a severe environmental problem. Thus, the utilization of these spent batteries, including the reuse of some components, is essential. The reusable components of the spent battery are carbon rods and electrolyte pastes. In this work, these components were utilized to prepare a carbon-based electrode for reverse electrodialysis. These electrodes can be an alternative to commercial Ti-based electrodes. The important characteristics of an electrode are the electrical conductivity, porosity, and surface area of the particles. This study aimed to determine the best electrical conductivity exhibited by various mixtures of carbon rods and electrolyte paste taken from spent batteries. The spent battery contained 95% carbon, and the electrolyte paste of the spent battery contained 64% carbon, 19% zinc, and 5% manganese. Before mixing, the carbon rods were powdered using ball mills for 4 h; 85.6% of particles were sized <1 μm. The best electrical conductivity was obtained from a mixture of carbon rods and electrolyte paste in the weight ratio of 7:2, with electrical conductivity, porosity, and surface area of 2.75 S/cm, 0.019 cc/g, and 15.936 m2/g, respectively.